The impact of the 2016 minimum wage increase on average labour costs, hours worked and employment in Irish firms - Paul Redmond; Séamus McGuinness (The Economic and Social Research Institute (ESRI), 2021)
In 2016, the Irish minimum wage increased from exteuro8.65 to exteuro9.15 per hour. A new ESRI study, funded by the Low Pay Commission, found that the 2016 minimum wage increase led to higher labour costs among firms with more than half of their employees on the minimum wage. However, these types of firms account for just 3 per cent of all firms. Compared to a firm with no minimum wage employees, a firm that pays all of their workers the minimum wage experienced a 5 per cent increase in their average weekly labour costs.
Keywords: 330; Mindestlohn; Wirkungsanalyse; Arbeitskosten; Irland